Implementasi Model Pembelajaran Aktif oleh Guru Dalam Meningkatkan Hasil Belajar Al-Qur’an Hadis di Madrasah Ibtidaiyah - Siregar, Yuliana; Hayati, Linda; Umayyah, Siti (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the low learning outcomes of students in the Al-Qur'an Hadith subject in Madrasah Ibtidaiyah, which is generally caused by the implementation of learning models that are still conventional and do not actively involve students. In fact, learning the Al-Qur'an Hadith not only emphasizes memorization aspects, but also understanding and practicing Islamic values. The purpose of this study is to examine in depth the implementation of active learning models by teachers in improving learning outcomes of the Al-Qur'an Hadith through a library research approach. This study uses a descriptive qualitative approach with a library study method. Data sources were obtained from scientific journals, reference books, and relevant educational documents. Data were analyzed using content analysis techniques with a theoretical and comparative synthesis approach to previous research results. The results of the study indicate that the active learning model through discussion, simulation, question and answer, and project methods has a positive impact on improving understanding, learning motivation, and the formation of students' religious character. The success of this strategy is highly dependent on the role of the teacher as a facilitator and designer of effective learning activities. This study also offers novelty in the form of the concept of value-based active learning, which is an active learning approach integrated with Islamic values. The implication of this study is the need for training for teachers in designing active learning and developing contextual and interactive teaching tools so that Al-Qur'an Hadith education in Madrasah Ibtidaiyah is more effective and meaningful.